2018
DOI: 10.1002/ejlt.201800151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Processing Methods of Iron Walnut Oils (Juglans sigillata): Lipid Yield, Lipid Compositions, Minor Components, and Antioxidant Capacity

Abstract: A comparison study is performed on different processing methods of iron walnut oils (Juglans sigillata). Processing methods here include cold‐pressing (CP), roasting‐pressing (RP), n‐hexane extraction (HE), subcritical butane extraction (SBE), and supercritical carbon dioxide extraction. The lipid yield, physicochemical properties, lipid compositions, minor components, and antioxidant capacity of iron walnut oils are analyzed. Different processing methods do not affect the fatty acid compositions and triacylgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 50 publications
8
32
1
Order By: Relevance
“…Roasting can release polyphenols from their bonds to various cellular components, thereby leading to polyphenols content increase . On the other hand, the Maillard reaction occurs in the walnut kernel due to roasting, which increased the amount of fat‐soluble phenolic compounds via the interaction of carbonyls with amines during thermal processing . Therefore, the polyphenols content in walnut oil was greatly increased.…”
Section: Resultsmentioning
confidence: 99%
“…Roasting can release polyphenols from their bonds to various cellular components, thereby leading to polyphenols content increase . On the other hand, the Maillard reaction occurs in the walnut kernel due to roasting, which increased the amount of fat‐soluble phenolic compounds via the interaction of carbonyls with amines during thermal processing . Therefore, the polyphenols content in walnut oil was greatly increased.…”
Section: Resultsmentioning
confidence: 99%
“…Many other oilseeds require the customized development of operation variables (Gao et al, 2018;Liu et al, 2019;Liu et al, 2020). These include oil refining from coconut, rice bran, rapeseed, and corn germ.…”
mentioning
confidence: 99%
“…Tocopherols of oils extracted by SFE, SP, and hexane were identified through a HPLC (LC‐20AT, Japan) using a silica column (4.6 × 250 mm, 5 μm, Jiangsu, China). Detector (SPD‐20A, Japan) set at 295 nm according to as described by Gao, Liu, Jin, and Wang (). Briefly, 1.0 g of oil was weighed and diluted by 10 mL of n‐hexane (chromatographic grade).…”
Section: Methodsmentioning
confidence: 99%
“…Phytosterols of oils extracted by SFE, SP, and hexane were identified by a GC–MS (Thermo Fisher) using a DB‐5 capillary column (Agilent, 30 m × 0.25 mm, 0.25 μm) according to procedures described by Gao et al (), and the contents of phytosterols were reported as mg/100 g.…”
Section: Methodsmentioning
confidence: 99%